Cardiovascular rehabilitation delivery and outcomes in Switzerland: data from a national database over the last decade. (3rd October 2022) - Tessitore, E; Schmid, J P; Hermann, M; Capoferri, M; Kiencke, S; Schmied, C; Tschanz, H; Wilhelm, M; Meyer, P
Abstract: Background: Cardiac rehabilitation (CR) is a multidisciplinary, comprehensive, exercise-based intervention strongly recommended by current guidelines to improve symptoms and quality of life and to reduce cardiovascular adverse outcomes, mainly in patients with coronary artery disease and heart failure. CR activities have not been reported on a Swiss national base so far. Purpose: To report CR outcome variables from a Swiss national base. Methods: As part of the Swiss working group for cardiovascular prevention, rehabilitation, and sports cardiology (SCPRS) quality standards, all Swiss CR centres provide yearly a quality indicator report on an online questionnaire. Annual data from 2010 to 2019 were transferred as medians or means of all individual patients' data from each centre. We used the t-Student test to compare changes of outcome variables between entry and exit of the programme. Results: A total of 133, 060 CR patients were included (68, 690 inpatients and 64, 370 outpatients) with a progressive increase reaching its climax with 14'909 patients/year in 2018. Mean age ± standard deviation (SD) in outpatient and inpatient programmes was 60±1 and 68±1 years, and women percentage 21% and 32%, respectively. The most common CR indication was acute coronary syndrome (51%) in outpatient, whereas cardiovascular surgery of various types (60%) was the main indication in inpatient programmes. Mean improvement ± SD of functional capacity was 38% ±3.6 using the six-minute walk test in inpatient (p<0.001) and 21% ±2 using cycle-ergometer maximal exercise testing in outpatient programmes (p<0.001). Quality of life mainly assessed with the 12-item Short Form Survey (SF-12) in outpatient CR improved by 13% ±4.5. MacNew Heart questionnaire systematically performed in inpatient programmes showed significant improvement at emotional level by 12% ±0.4, at physical level by 30% ±0.9, and at social level by 18% ±0.6. Conclusion: Even if still underutilised in certain groups of patients such as women or heart failure, CR has gained growing importance in Switzerland during the last decade. Functional capacity, as well as quality of life, was significantly improved. Individual CR patient data should be collected in the future to improve assessment of outcome parameters and benchmarking of centres. Funding Acknowledgement: Type of funding sources: None.